Uji Efektivitas Larvasida Bacillus thuringiensis var. israelensis Terhadap Kematian Larva Aedes - Hitipeuw, Derico; Martini, Martini; Hestiningsih, Retno; Udijono, Ari (Jurnal Riset Kesehatan Masyarakat, 2022)
Dengue Hemorrhagic Fever is an infectious disease that often causes outbreaks. In Indonesia, the CFR of DHF in 2021 reached 0.96%, this figure increased from the previous year, which was 0.69%. Various efforts have been made to prevent transmission of the dengue virus, for example the use of larvicides for the eradication of Aedes, as a vector for transmitting dengue. The type of research in the Bio Larvicide B. Thuringiensis test is a pure experiment with a posttest only control design. The study was conducted to determine the effect of giving B. thuringiensis on the mortality of A. aegypti larvae in conditions that almost resembled their natural habitat. The study population was all larvae of Aedes instar III from the colonies of the Salatiga B2P2VRP Laboratory. Sampling was done randomly/simple random, ie all third instar larvae had the opportunity to be used as research and control samples. The mortality of Aedes larvae from the intervention of VectoBac WG (Bio Larvicide with the active ingredient B. thuringiensis) from each concentration at 60 minutes of observation, namely the mortality of Aedes larvae in the control group was 0%, at a concentration of 0.001 g/L was 93%, at a concentration of 0.002 g/L as much as 98%, a concentration of 0.004 g/L, 0.006 g/L and 0.008 g/L as much as 100%. The results of this study can be used as a reference for the use of VectoBac WG products as natural larvicides and an alternative in controlling mosquito vector populations.